1991
DOI: 10.1007/bf00169544
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine4 receptors mediate relaxation of the rat oesophageal tunica muscularis mucosae

Abstract: The present study was designed to characterize an "atypical" 5-hydroxytryptamine (5-HT) receptor mediating relaxation of the rat oesophageal tunica muscularis mucosae. All experiments were performed under equilibrium conditions, using pargyline to inhibit the oxidative deamination of indoleamines, and cocaine and corticosterone to inhibit neuronal and extraneuronal uptake. Under these conditions 5-HT (0.3-1000 nmol/l) produced a concentration-dependent relaxation of carbachol-induced tension. The concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
106
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(125 citation statements)
references
References 24 publications
18
106
1
Order By: Relevance
“…The affinity of RS 23597-190 at 5-HT4 receptors was determined on the rat isolated oesophageal muscularis mucosae (Baxter et al, 1991). All tissues were suspended in Krebs physiological salt solution of the following composition (mM): NaCl 139.0, KCI 2.7, MgCl2.6H20 1.1, NaH2PO4 0.4, glucose 5.6, NaHCO3 11.8 and CaC12.6H20 1.8.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The affinity of RS 23597-190 at 5-HT4 receptors was determined on the rat isolated oesophageal muscularis mucosae (Baxter et al, 1991). All tissues were suspended in Krebs physiological salt solution of the following composition (mM): NaCl 139.0, KCI 2.7, MgCl2.6H20 1.1, NaH2PO4 0.4, glucose 5.6, NaHCO3 11.8 and CaC12.6H20 1.8.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…All tissues were suspended in Krebs physiological salt solution of the following composition (mM): NaCl 139.0, KCI 2.7, MgCl2.6H20 1.1, NaH2PO4 0.4, glucose 5.6, NaHCO3 11.8 and CaC12.6H20 1.8. When precontracted with carbachol (3 PM), this preparation is relaxed by 5-HT via 5-HT4 receptor-mediated stimulation of adenosine 3':5'-cyclic monophosphate (cyclic AMP) production (Baxter et al, 1991;Ford et al, 1992 (Baxter et al, 1991). These experiments were repeated with the non-indole 5-HT4 agonists, renzapride and SC-53116 in order to assess the agonist dependence of the affinity for RS .…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In the gut, rat oesophagus muscularis mucosae contains smooth muscle 5-HT 4 receptors mediating relaxation (Baxter et al, 1991), an e ect suggested to be absent in the guinea-pig and dog (Cohen et al, 1994). In the human lower oesophageal sphincter, there is evidence for the presence of excitatory 5-HT 4 receptors on the cholinergic nerves (Tomita et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Rat isolated oesophageal muscularis mucosal studies 5-HT4 agonist activity was studied in the rat isolated oesophagus (Baxter et al, 1991), in which relaxation is mediated by 5-HT4 receptor activation. Thoracic oesophagus was isolated from male Sprague-Dawley rats (Charles River,) and placed in Tyrode solution (composition, mM: NaCl 139.0, KCl 2.7, MgCl2.…”
Section: Introductionmentioning
confidence: 99%